Notes on some sertulariid hydroids (Cnidaria: Hydrozoa) from the tropical western Pacific, with descriptions of nine new species - Galea, Horia R. (European Journal of Taxonomy, 2016)
Forty-three species of sertulariid hydroids (Cnidaria: Hydrozoa: Sertulariidae), collected from the tropical western Pacific (Taiwan, Philippines, New Caledonia, French Polynesia, Vanuatu, Fiji, Tonga, Solomon Islands) during various expeditions of the French Tropical Deep-Sea Benthos program, are discussed. Of these, nine are new to science: Gonaxia nova sp. nov., G. plumularioides sp. nov., Sertularella folliformis sp. nov., Se. plicata sp. nov., Se. pseudocatena sp. nov., Se. splendida sp. nov., Se. tronconica sp. nov., Se. tubulosa sp. nov., and Symplectoscyphus paucicatillus sp. nov. The subspecies Symplectoscyphus johnstoni (Gray, 1843) tropicus Vervoort, 1993 is raised to species but, in order to avoid the secondary homonymy with Sy. tropicus (Hartlaub, 1901), the replacement name, Sy. fasciculatus nom. nov., is introduced. The male and female gonothecae of Diphasia cristata Billard, 1920, the male gonothecae of Gonaxia elegans Vervoort, 1993, as well as the female gonothecae of Salacia macer Vervoort & Watson, 2003, are described for the first time. Additional notes on the morphology of several other species are provided. All taxa are illustrated, in most cases using figures drawn at the same scale, so as to highlight the differences between related species.